Mass loss of the Greenland ice sheet until the year 3000 under a sustained late-21st-century climate - Ralf Greve; Christopher Chambers (Journal of Glaciology, 2022)
We conduct extended versions of the ISMIP6 future climate experiments for the Greenland ice sheet until the year 3000 with the model SICOPOLIS. Beyond 2100, the climate forcing is kept fixed at late-21st-century conditions. For the unabated warming pathway RCP8.5/SSP5-8.5, the ice sheet suffers a severe mass loss, which amounts to ~ 1.8 m SLE (sea-level equivalent) for the 12-experiment mean, and ~ 3.5 m SLE (~ 50% of the entire mass) for the most sensitive experiment. For the reduced emissions pathway RCP2.6/SSP1-2.6, the mass loss is limited to a two-experiment mean of ~ 0.28 m SLE. Climate-change mitigation during the next decades will therefore be an efficient means for limiting the contribution of the Greenland ice sheet to sea-level rise in the long term.